Merit-order effect of wind generation in the Philippines is wind integration related to lower electricity price? - Pleto, Wilhelmina M.
This paper aims to determine the impact of the merit order effect of wind energy generation to the wholesale electricity spot prices and electricity prices to consumers in the Luzon grid. The study made simulations using Wholesale Electricity Spot Market data for the period of December 26, 2014 to December 25, 2016. Retrospective approach and regression model were considered and it was found that the retrospective model was more suitable to use in estimating the merit order effect of wind integration on electricity spot prices in the Philippines. Based on the retrospective model results, the weighted average merit order effect of wind integration in the Luzon grid is about Php 634.48 / MWh. By rate impact analysis, it was calculated that this merit order effects results in electricity price overall savings ranging from Php 0.03/kWh up to PhP 0.07/kWh to the consumers. This calculations includes effect in generation charge and in Feed-in Tariff Allowance. By using general linear model, the predictor variables used consisted of the historical wind generation, Luzon demand, average of non-zero bid prices of coal, gas and oil. Three models were generated based on the level of wind penetration - low -level (0 MW to 50 MW), mid-level (51 MW to 131 MW) and high-level (132 MW to 331 MW) wind penetration. The R-squared for the three models are 15.38%, 15.08% and 18.63% for low-level, mid-level and high-level wind penetration, respectively, compared to an average R-squared of 38% (ranging from 34% to 46%) from previous studies. The low level of R-squared indicated that an about 15.08% to 18.63% of variation in market clearing prices is explained by the regression model. Thus, the retrospective model was applied further in the rate impact analysis. In summary, merit-order effect of wind generation was observed in the Luzon region of the Philippines. This indicates that wind integration in the electricity grid and power market depresses the market clearing prices and the overall electricity prices of the consumers.